Використовуючи метод заміщення, як ви вирішуєте 4x + y + 5z = -40, -3x + 2y + 4z = 1 і x-y-2z = -2?

Використовуючи метод заміщення, як ви вирішуєте 4x + y + 5z = -40, -3x + 2y + 4z = 1 і x-y-2z = -2?
Anonim

Відповідь:

Рішення: # x = 3, y = 43, z = -19

Пояснення:

# 4x + y + 5z = -40 # (1)

# -3x + 2y + 4z = 1 # (2)

# x-y-2z = -2 # (3) #:. y = x-2z + 2 #

Введення # y = x-2z + 2 # у формулі (2) і (3) отримуємо, # 4x + x-2z + 2 + 5z = -40 або 5x + 3z = -42 (4) і

# -3x + 2 (x-2z + 2) + 4z = 1 або -x = 1 -4:. x = 3 #

Введення # x = 3 # у рівнянні (4) отримаємо # 5 * 3 + 3z = -42 #

або # 3z = -42-15 або 3z = -57 або z = -19 #

Введення # x = 3, z = -19 # у рівнянні (1) отримуємо, # 4 * 3 + y + 5 * (- 19) = -40 або y = -40-12 + 95 = 43 #

Рішення:# x = 3, y = 43, z = -19 Ans